Influence of the oil palm trunk and acacia mangium on the particleboard Properties / Abdul Hakim Baihaqi Mohamad Noor, Zaimatul Aqmar Abdullah and Said Ahmad - Mohamad Noor, Abdul Hakim Baihaqi; Abdullah, Zaimatul Aqmar; Ahmad, Said (2015)
The objective of this study was to evaluate both physical and mechanical properties of particleboard from all palm trunk (Elais guineensis) and Acacia mangium when using phenol formaldehyde adhesive. For this study the bottom part from both species had been used and the target board density was fixed at 650kg/m3. Experimental boards were from 100% OPT, 100% Acacia and 50:50 mixture of OPT and Acacia. Resin content variations of 7%, 9% and 11% were applied on each combination. Modulus of rupture (MOR), modulus of elasticity (MOE), internal bonding strength (IB), density (p) thickness swelling (TS) and water absorption (WA) of the samples were tested based on European Standard (EN). Panels made with 100% Acacia particles had the highest average for both modulus of rupture (MOR) strength and internal bonding at 11.94 MPa and 0.37 MPa respectively. Mixture of Acacia and OPT in the boards influenced their physical properties in bolt TS and WA. Based on this research it is shown that both species have potential to be used as raw materials for particleboard.